Differentiation or dialectic: pluralism and contestation in European economic constitutionalism - Marija Bartl; Paul Linden-Retek (European Law Open)
In this contribution we ask how Přibáň’s theoretical choices shape the capacity of ‘European constitutional imaginaries’ to account for the ever more necessary work of recognition and redistribution within European society. While ‘European constitutional imaginaries’ reveal the intricate ideologies at play within European law and politics, as well as their power in motivating dominant currents of European political life, the project remains limited in that it accepts essential tenets of functional differentiation in society, obscuring the conditions of possibility for the formation of differentiated systems. Put differently, ‘European constitutional imaginaries’, both as forms of life and analytic concepts, have difficulty in conceiving the frontiers of imaginaries, their beginning and end, their formation and transformation—and in so doing, risk naturalizing their initial differentiation as a priori excluded from political contestation.